Effect of enterovirus D68 on Lung Clearance Index in patients with cystic fibrosis: A case report. (2015) - Goetz, Danielle M.; Singh, Shipra; Sheehan, Daniel
Abstract: Cystic fibrosis (CF) causes airways obstruction and a decline in percent predicted forced expiratory volume in 1 s (FEV1 %). FEV1 % is an objective measure of a pulmonary exacerbation of CF; improvement in FEV1 % is the endpoint used often to determine success of treatment of these acute declines in pulmonary health. Lung Clearance Index (LCI), derived from multiple breath inert gas washout (MBW) test, measures ventilation inhomogeneity and small airways dysfunction. In the United States in 2014–2015, enterovirus D68 (EV-D68), a novel virus, led to hospitalizations in children because of respiratory distress. This report describes 2 patients with CF admitted for pulmonary exacerbations who were enrolled in an inpatient study to assess patient satisfaction and utility of MBW to measure LCI. Diagnostic testing indicated that these patients were infected with EV-D68. Although their FEV1 % improved to their previous baseline following treatment for pulmonary exacerbation, it was discordant with LCI. We discuss LCI as a novel measure of pulmonary function and hypothesize that, based on these cases, it may be a more sensitive indicator of ongoing post-viral airways dysfunction as compared to FEV1 %.